Structural and Superconductivity Properties of BaFe2-xPtxAs2 - GÜLER, ADİL; BOYRAZ, CİHAT (SPRINGER, 2017)
Extraordinary magnetic behaviors, resistivity properties, and lattice parameters of the main sample BaFe2As2 and BaFe2-xPtxAs2 in the variation of x from 0 to 0.4 with the step of 0.1 were investigated. The bulk materials have been prepared by the solid-state reaction method and sealed into a quartz tube. The crystal structure of all samples exhibited the ThCr2Si2-type crystal structure which is in harmony with earlier studies in the literature. The superconducting states with magnetization measurements have been detailed in the wide temperature range 5-170 K, up to a field of 20 Oe. Increasing Pt and decreasing Fe elements in the BaFe2-xPtxAs2 compound deteriorated superconductivity. Using magnetization measurement data, we present the variation of superconducting critical temperature (T-c) correlating with a Pt dopant rate from x = 0 to x = 0.4. The dopant rate of x = 0.3 exhibited the limit rate for maximum Tc; deterioration of superconductivity was revealed with a dopant rate of more than x = 0.3. This should be explained by varying Tc related to a lattice shrinking and pressure effect (geometric factor).
Keywords: Lattice shrinkage; Geometric factor; Meissner effect; Pt dopant effect; Superconductivity; HIGH-TEMPERATURE SUPERCONDUCTIVITY